Unethical audit behaviour among Malaysian auditors: an exploratory study - Mohd Nor, Mohd Nazli; Smith, Malcolm Smith; Ismail, Zubaidah; Nahar, Hairul Suhaimi (Universiti Putra Malaysia Press, 2015)
The purpose of this paper is to investigate the occurrence of unethical behaviours commonly known as Reduced Audit Quality Practices (RAQP) among auditors. The study employed a mail survey to collect data from auditors registered with the Malaysia Institute of Accountants. The results of this study indicated that RAQP did occur in the Malaysian auditing profession, especially among auditors with less auditing experience and practicing in non-big four audit firms.